ANALISIS STRATEGI PROMOSI ONLINE, HARGA ONLINE DAN KUALITAS SDM DALAM MENINGKATKAN PENJUALAN UMKM WITROVE - Vera Maria; Adip Putra Gemilang; Laras Elvira Nurariva (Bajang Institute, 2022)
Micro, Small and Medium Enterprises (MSMEs) are one of the business units that play an important role in economic growth and development as well as the welfare of the people in Indonesia. Promotion is a way for companies to communicate both business and to many people so that consumers are interested in buying the products offered. The research used is an approach and the data used in this study is primary data, namely data obtained directly from sources. The results obtained from this research are from Witrove's promotional strategy to promote its business with Surabaya Fashion Week (SFW) in collaboration with the local government. Witrove also collaborated with several well-known influencers to promote their products. Then there was a price gap between the Witrove business and its competitors in the marketplace, causing no purchases of Witrove business products. Furthermore, the quality of Witrove's human resources is still less competent in terms of managing social media accounts and in the activeness of its admin marketplace.